Retracted: Prenatal and neonatal complications of COVID‐19: A systematic review - Zahra Pashaei; SeyedAhmad SeyedAlinaghi; Kowsar Qaderi; Alireza Barzegary; Amirali Karimi; Seyed Peyman Mirghaderi; Pegah Mirzapour; Marcarious M. Tantuoyir; Omid Dadras; Zoha Ali; Fabricio Voltarelli; Esmaeil Mehraeen (Health Science Reports, 2022)
Abstract Background and Aims The outbreak of coronavirus disease 2019 (COVID‐19) over the past year has affected public health worldwide. During pregnancy, the maternal immune system and inflammatory responses are widely suppressed. Pregnancy‐related immune system suppression could make the mother vulnerable to infectious diseases like SARS‐COV‐2. However, current data suggest little to no possibility of COVID‐19 transmission in pregnant women to the fetus during pregnancy or childbirth. This systematic review focused on the possible complications of COVID‐19 infection in the fetus and newborn babies including the possibility and evidence of vertical transmission by reviewing articles published during the first year of the COVID‐19 pandemic. Methods We conducted a systematic search using keywords on PubMed, Embase, and Scopus databases. The studies followed a title/abstract and a full‐text screening process, and the eligible articles were included in the study. Results In total, 238 published papers were identified using a systematic search strategy (44 articles met the inclusion criteria and were included in the final review). In all studies, a total of 2375 women with signs and symptoms of COVID‐19, who were in the second and third trimester of pregnancy, were assessed mild to moderate pneumonia was one of the most common symptoms. Seventy‐three percent of the women did not present any comorbidity, 19% had a fever, 17% had to cough as the most frequent clinical signs and symptoms, 7.5% had pulmonary changes with chest scans, 8% had increased C reactive protein, and 9.4% had decreased lymphocytes (lymphocytopenia). A total of 2716 newborns and fetal were assessed; the delivery method of 1725 of them was reported, 913 (53%) through C‐section delivery, and 812 through normal vaginal delivery (47%). Of total newborns, 13 died (five died along with the mother), and 1965 were tested for SARS‐CoV‐2:118 tested positive. In a study, vertical transmission in seven cases was reported in total of 145 cases assessed. Conclusion It appeared that most pregnant COVID patients were mildly ill, and there is currently no convincing evidence to support the vertical transmission of COVID‐19 disease. Therefore, neonates do not represent any additional risk for adverse outcomes neither during the prenatal period nor after birth.